La lunga decolonizzazione delle città africane (Altre Modernità, 2016)
The political project of decolonization was based on a "total, complete, and absolute substitution" (Fanon) of a system with another, but in the urban geography of Sub-Saharan Africa this process has been long, complex and not without ambiguity. On one hand, we observe a radical discontinuity in place names, in the administrative structure and in the monumental landscape of African cities; on the other, postcolonial urban planning and architecture showed strong continuity with the colonial functionalist model. In recent African urban projects as well, we observe the action of a colonial rationality, based on the removal of existing territories and on the production of standardized and fragmented urban spaces.